Pengaruh Implementasi Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan di Rumah Sakit X di Bandung (Jurnal Riset Manajemen dan Akuntansi, 2025)
Financial statements are an important communication tool for interested parties in an organization, including hospitals. The accuracy and transparency of financial statements can be influenced by the implementation of the Accounting Information System (SIA) and the effectiveness of internal controls. This study aims to analyze the influence of SIA and internal control on the quality of financial statements in a private hospital that has recently implemented integrated SIA. This study uses a quantitative method with a survey approach. Data was collected through the distribution of questionnaires to 39 respondents consisting of employees of related hospitals. One of the analysis models used is multiple linear regression to test the relationship between independent variables, namely SIA (X1) and internal control (X2), to dependent variables, namely the quality of financial statements (Y). The results of the study show that SIA has a positive influence on the quality of financial statements, which is shown by the ease of recording transactions, increased efficiency in report preparation, and increased accuracy of financial data. In addition, internal control also plays a significant role in improving the quality of financial statements through supervision mechanisms, authorization systems, and risk evaluations implemented by management.